Exploring the Textual Journey: Building Bridges between Early Childhood and Primary Education. - Madrid-Vivar, Dolores; Molina-García, Mª José; Pascual-Lacal, María del Rocío (Asociación Española de Comprensión Lectora y Universidad de Málaga, 2024)
This research forms part of the European Project “READ-COM: Reading Communities from paper books to digital era”. Its objective is to raise awareness of the importance of reading and to provide innovative resources to improve reading practices in homes and schools. In particular, it examines the similarities and differences in the textual typology used by early childhood and primary school teachers. A quantitative study was conducted with the participation of 440 teachers, 200 from the second cycle of infant education and 240 from primary education. The findings of this study revealed notable differences in the selection of texts used by pre-school and primary school teachers. It was observed that enumerative, expository, and literary texts were used differently at both stages, indicating that pedagogical approaches may vary. Conversely, no significant variations were found in the use of prescriptive and informative texts. These findings suggest the need for greater coordination and communication between the pre-primary and primary levels to ensure a more effective transition in the teaching of reading and textual comprehension. Furthermore, they underline the importance of providing innovative resources that encourage textual diversity in the classroom, in line with this project, to enrich reading practices both at home and in schools.
Exploración del viaje textual: construcción de puentes entre la educación infantil y primaria.
Keywords: Lectura; Enseñanza primaria; Educación infantil; Text typology; Reading; Early childhood education; Primary education; Teacher